Inter layer and cooperative design strategies for green mobile networks - Alam, Muhammad (2014)
The promise of a truly mobile experience is to have the freedom to roam around anywhere and not be bound to a single location. However, the energy required to keep mobile devices connected to the network over extended periods of time quickly dissipates. In fact, energy is a critical resource in the design of wireless networks since wireless devices are usually powered by batteries. Furthermore, multi-standard mobile devices are allowing users to enjoy higher data rates with ubiquitous connectivity. However, the bene ts gained from multiple interfaces come at a cost in terms of energy consumption having profound e ect on the mobile battery lifetime and standby time. This concern is rea rmed by the fact that battery lifetime is one of the top reasons why consumers are deterred from using advanced multimedia services on their mobile on a frequent basis. In order to secure market penetration for next generation services energy e ciency needs to be placed at the forefront of system design. However, despite recent e orts, energy compliant features in legacy technologies are still in its infancy, and new disruptive architectures coupled with interdisciplinary design approaches are required in order to not only promote the energy gain within a single protocol layer, but to enhance the energy gain from a holistic perspective. A promising approach is cooperative smart systems, that in addition to exploiting context information, are entities that are able to form a coalition and cooperate in order to achieve a common goal. Migrating from this baseline, this thesis investigates how these technology paradigm can be applied towards reducing the energy consumption in mobile networks. In addition, we introduce an additional energy saving dimension by adopting an interlayer design so that protocol layers are designed to work in synergy with the host system, rather than independently, for harnessing energy. In this work, we exploit context information, cooperation and inter-layer design for developing new energy e cient and technology agnostic building blocks for mobile networks. These technology enablers include energy e cient node discovery and short-range cooperation for energy saving in mobile handsets, complemented by energy-aware smart scheduling for promoting energy saving on the network side. Analytical and simulations results were obtained, and veri ed in the lab on a real hardware testbed. Results have shown that up to 50% energy saving could be obtained.